2.25x+4.50=1.75x+6

Simple and best practice solution for 2.25x+4.50=1.75x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.25x+4.50=1.75x+6 equation:


Simplifying
2.25x + 4.50 = 1.75x + 6

Reorder the terms:
4.50 + 2.25x = 1.75x + 6

Reorder the terms:
4.50 + 2.25x = 6 + 1.75x

Solving
4.50 + 2.25x = 6 + 1.75x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.75x' to each side of the equation.
4.50 + 2.25x + -1.75x = 6 + 1.75x + -1.75x

Combine like terms: 2.25x + -1.75x = 0.5x
4.50 + 0.5x = 6 + 1.75x + -1.75x

Combine like terms: 1.75x + -1.75x = 0.00
4.50 + 0.5x = 6 + 0.00
4.50 + 0.5x = 6

Add '-4.50' to each side of the equation.
4.50 + -4.50 + 0.5x = 6 + -4.50

Combine like terms: 4.50 + -4.50 = 0.00
0.00 + 0.5x = 6 + -4.50
0.5x = 6 + -4.50

Combine like terms: 6 + -4.50 = 1.5
0.5x = 1.5

Divide each side by '0.5'.
x = 3

Simplifying
x = 3

See similar equations:

| 8s-16-5s=-5 | | 10-x=3(x-6) | | 6-a/3=2 | | 6+2.5+6+2.5= | | 0.7x+0.6(12-x)=47 | | 7+4p=19 | | F(h(x))=x^2+7 | | V-4=5+5v+3 | | 29=-9v+9-v | | -9m-3=78 | | 5+x-4x=-1 | | 8x-2(3x-5)=3x+15 | | -3-8x=-10-2x-7x | | 2x-5(x-4)=-3+4x-12 | | -6b-8=19 | | 4g-6-9=3 | | 3=5-2a | | 8x-1=8(x-3) | | 5x+8(-4x-9)=-10(-2x-9)+26 | | x^2-6x-96=0 | | 2k-1=-5+3k | | 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 | | 7x+5x-38=95-7x | | 2k-1=-5+2k | | 5b-13=3b+1 | | t=6s+18.01 | | 5z+30=40 | | 5-3p+9=13p+8 | | 3f+2=5 |

Equations solver categories